Significant Association Between Obsessive-Compulsive Disorder And Atopic Dermatitis - A Retrospective Population-Based Case-Control Study - Sofia Åkerlund; Oliver Seifert; Johan Assarsson; Sandra Gulin-Jerkovic (Mattioli1885, 2023)
Introduction: Atopic dermatitis (AD) is a global health problem. There are no data on the association of AD with obsessive-compulsive disorder (OCD). Objectives: This study aimed to map a wide spectrum of different diseases among patients with atopic dermatitis compared to healthy controls in the Region of Jönköping County, Sweden with special focus on OCD. Methods: We conducted a retrospective case control study from January 1st 2013 until December 31st 2021 using an electronic medical records database covering the entire population of the County of Jönköping. ICD-10 codes were used to identify patients with AD. Individuals without AD served as controls. A total number of 398,874 citizens under the age of 90 was included in this study and among these 2,946 individuals were diagnosed with AD. Regression analysis was performed to describe the risk for comorbidities in patients with AD compared to controls, adjusted for age and gender. Results: We found an association between obsessive-compulsive disorder (OCD) in patients with AD (adjusted odd ratio 2.0, 95% confidence interval 1.5-2.7, p<0.001). Other results are in the line with other studies. Conclusion: Pointing to previous studies, the cause of AD and OCD share several gene-environmental mechanisms and this association should be further studied on larger populations. The results of the present study underline the need for dermatologists to be aware of OCD and to screen for this condition in AD patients because early diagnosis and treatment may improve outcome.